Consenting or yielding? An analysis of Vanessa Springora’s work : Le Consentement (Grasset, 2020) - Pena López, Claudia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The present study analyses consent through the eyes of Vanessa Springora in her novel Le Consentement (Grasset, 2020), translated into Spanish as El consentimiento (Lumen, 2021). The author proposes a factual account of the relationship she had in the 1980s with the writer Gabriel Matzneff. The absence of judgment in the words of a 13-14 year old girl, persecuted by a sexual predator of 50, endows the work of Springora with a damning dimension. The author questions the notion of ‘consent’ and criticizes the intellectual milieu of post-May 1968 France.